Optical inspection of the braid formation zone during manufacturing of preforms from reinforcement fibers for defect detection purposes - Maidl, Stephan; Hilbck, Maximilian; Kind, Kalle; Drechsler, Klaus (Frontiers in Materials, 2023)
Braiding is a highly automated process for manufacturing preforms directly from reinforcement yarns at large production volumes. The quality of braided textiles and the stability of the process can however be negatively affected by defects that occur during braiding. If such defects can be detected from fine process anomalies early during their formation, the process can be interrupted and countermeasures can be introduced before the defect aggravates and gets braided into the product. Current sensor modules for defect detection during braiding however involve problems of either late response times, process impairments or a lack of applicability to braiding of composite parts. In an effort to overcome these drawbacks, the paper at hand proposes to optically monitor the braid formation zone by means of a single camera (no process impairments). An associated image analysis algorithm creates a measure for the angular distance of each individual braiding yarn to its neighboring yarns and tracks the yarns as they rotate around the overbraidable mandrel (typical for braiding of composite parts). Since braiding yarns typically exhibit distinct curvatures as they span from the bobbins towards the center of the braiding machine due to frictional yarn-yarn interaction, a change in yarn curvature and thus in angular yarn distance is an early sign of a defect-characteristic anomaly in yarn tension (early response). If implemented on a real-time capable computing device, an apparatus according to the presented method can be retrofitted to existing production lines for braiding process monitoring. It then contributes to the reduction of error correction times since countermeasures are quicker to implement as long as the defect has not aggravated, yet. Furthermore, scrap material rates can be reduced as anomalies can be detected before they manifest in the braided structure.